Complex NF-kappaB interactions at the distal tumor necrosis factor promoter region in human monocytes. - Udalova, I; Knight, J; Vidal, V; Nedospasov, SA; Kwiatkowski, D (1998)
We describe a dense cluster of DNA-protein interactions located 600 nucleotides upstream of the transcriptional start site of the human tumor necrosis factor (TNF) gene. This area was identified as being of potential importance for lipopolysaccharide-inducible TNF expression in the human monocyte cell line Mono Mac 6, based on reporter gene analysis of point mutations at a number of nuclear factor kappaB (NF-kappaB)-like motifs within the human TNF promoter region. The area contains two NF-kappaB sites, which are here shown by DNase I and methylation interference footprinting to flank a novel binding site. UV cross-linking studies reveal that the novel site can also bind NF-kappaB as well as an unknown protein(s) of approximately 40 kDa. We show that these three adjacent kappaB-binding sites differ markedly in their relative affinities for p50/p50, p65/p65, and p65/p50, yet this 39-nucleotide segment of DNA appears capable of binding up to three NF-kappaB heterodimers simultaneously. Reporter gene studies indicate that each element of the cluster contributes to lipopolysaccharide-induced transcriptional activation in Mono Mac 6 cells. These findings suggest that NF-kappaB acts in a complex manner to activate TNF transcription in human monocytes.